PATHOMORPHOLOGICAL DIAGNOSIS OF SEPTIC DISEASES - Kuliev B.,; S.Akhmedov, (TADQIQOTLAR, 2025)
Abstract:  This  article  describes  the  pathomorphological  diagnosis  of colibacteriosis, salmonellosis and pasteurellosis in farm animals. The purpose of this topic is to create and introduce a local drug (vaccine) to prevent and fight against these diseases.